Submucosal Lingualplasty for Adult Obstructive Sleep Apnea. Issue 1 (26th September 2012) - Gunawardena, Indunil; Robinson, Sam; MacKay, Stuart; Woods, Charmaine M.; Choo, June; Esterman, Adrian; Carney, A. Simon
Abstract : Objective: To measure quality‐of‐life outcomes, polysomnographic outcomes, and adverse effects for a new technique of tongue reduction in obstructive sleep apnea. Study Design: Case series. Setting: Tertiary hospital. Subjects and Methods: Consecutively treated adult patients (N = 27) with obstructive sleep apnea having submucosal lingualplasty in 2007 were studied. All had concurrent or previous uvulopalatoplasty ± palatal advancement. Full polysomnography preoperatively and 3.7 ± 0.4 months postoperatively, scored using the American Academy of Sleep Medicine 2007 criteria, was recorded. Snoring severity score, Epworth Sleepiness Scale, and complication data were collected at a 2.61 ± 0.08‐year follow‐up via questionnaire. Results: Mean snoring severity score fell from 7.1 ± 0.4 to 2.3 ± 0.6 ( P <. 05). Epworth Sleepiness Scale score fell from 8.3 ± 1.1 to 5.8 ± 1.0 ( P <. 05). The apnea‐hypopnea index (AHI) fell from 44.0 ± 4.3 to 12.5 ± 2.3 ( P <. 05). Success, defined as achieving an AHI <15 postoperatively, was observed in 74% (20/27), with each of these patients achieving a reduction in AHI >50%. Lowest oxygen saturation improved from 84 ± 1 to 88 ± 1 ( P <. 05). Pain was mild to moderate. Short‐term postoperative complications included bleeding (3.7%) and infection (14.8%). Some minor long‐term (6 months) alteration in tongue function was reported with regard to speech (47%), swallow (33%), and taste (33%). Conclusion: Submucosal lingualplasty with concurrent palatal surgery is a promising treatment option in adult patients with obstructive sleep apnea with macroglossia.